Demography and Clinical Characteristic COVID-19 with Diabetes Mellitus at the Universitas Sumatera Utara Hospital - Mikhael Kurnia S.J. Situmorang; Brama Ihsan Sazli (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Background: COVID-19 is a disease caused by a virus called SARS-CoV-2. COVID-19 can infect almost all age groups, however, the elderly and those with co-morbidities such as diabetes mellitus can get worse complications from COVID-19. The study aims to find out the demographics and clinical characteristics of COVID-19 patients with diabetes mellitus treated at the Universitas Sumatera Utara Hospital. Method. This research is a descriptive study using retrospective data. The data used is secondary data taken from medical records. The number of samples that met the inclusion criteria was 37 people. Results. The majority of patients were dominated by the age group of 46-65 years (56.8%) and males (54.1%). The predominating clinical characteristics of COVID-19 with diabetes mellitus are cough (70.3%), shortness of breath (59.5%), and fever 51.4%. There was an increase in the laboratory results of COVID-19 patients with diabetes mellitus on blood sugar levels at admission, HbA1c, urea, creatinine, SGOT, SGPT, and d-dimer levels. The most treatment results were recovered by as many as 24 people (64.9%). Conclusion. The majority of patients are in the age group of 46-65 years and are male. The most common clinical characteristic is cough and there is an increase in laboratory results in patients